Popular resistance in Tanzania : lessons from Sungu Sungu - Campbell, Horrace
This was a paper presented to the International Seminar on Internati onal Conflict held on 21st-25th September, 1987.
AR/MISR/51/1/1
English
Shelf no. 1.
Keywords: Political parties -- Tanzania; Tanzania -- Politics and government